Exploring the potential of mass tourism in the facilitation of community development : a case study of Jiuzhaigou Biosphere Reserve, Western China : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University, New Zealand - Dombroski, Kelly (Massey University, 2005)
It is not generally thought that there is great potential for sustainable and empowering local-level development through mass tourism; however the majority of world tourism continues to be at the large scale. This is especially so in China, where mass tourism is pursued as a means of developing the western regions where ethnic minority groups mostly reside. Instead of advising only small-scale community tourism based on theories of participation and empowerment, there is a need to examine realistically the potential of mass tourism for local-level development that is both sustainable and empowering. This thesis uses the case study of Jiuzhaigou Biosphere Reserve, Sichuan, China to explore the possibilities for the development of resident Tibetan communities hosting more than a million Chinese tourists per year. According to the values of the Tibetan village Panyazhai, well-being has indeed been enhanced through mass tourism, in a manner that is moving towards sustainability and empowerment. The thesis concludes that in Jiuzhaigou regulation is the key to sustainable and empowering development, and appropriate regulation is best achieved through partnerships between local communities and the State that involve both formal and personal relationships.
Keywords: Tourism -- China; Case studies; Jiuzhaigou Ziran Baohuqu; Sustainable development